EVALUATION OF INVENTORIES ACCORDING TO THE STANDARDS OF ACCOUNTING - Etleva Peta (European Scientific Journal, ESJ, 2013)
The realization of the economic enterprise of every economic unit is a complex problem and a result of the cooperation of many factors of social and material character. In addition to the use with effectiveness of the material and technical basis which form the long term assets which the economic unit has at its disposal, before and during its functional process, a special importance but also important take also the long term assets among which are the inventories. The process of inventory valuation is important for the economic unit, to ensure a real presentation of financial review. For this condition to be met a very important element is the implementation of the National Standards of Accounting. The valuation of inventories according to SKK is related with the selection of basic methods which will be used for their valuation.